A breath of fresh air: Validity and reliability of a Portuguese version of the Multidimensional Dyspnea Profile for patients with COPD - Belo, Letícia F. (PLoS One, 2019)
AIM: To provide a Portuguese version of the Multidimensional Dyspnea Profile (MDP), investigating its validity and reliability in Brazilian patients with COPD. METHODS: This was a cross-sectional study for translation and linguist validation of the Portuguese MDP version for patients with COPD. The process occurred according to the protocol of Mapi Research Trust, Lyon, France. Three scores of MDP were used for the analysis: the immediate unpleasantness of dyspnea (A1); the “immediate perception domain” (S) (sum of A1 plus the sensory descriptors) and the “emotional response domain” (A2) (sum of the emotional descriptors). The questionnaires COPD assessment Test (CAT), Hospital Anxiety and Depression scale (HADS) and Medical Research Council scale (MRC) were used as anchors to investigate MDP’s validity. Internal consistency was assessed with Cronbach’s alpha. Test–retest reliability was assessed with intraclass correlation coefficient (ICC) and concurrent validity was assessed with Spearman correlation coefficients. RESULTS: Thirty patients with moderate-severe COPD were studied for MDP’s validation analysis (43% male, 63±8years, body mass index [BMI] 27±6Kg/m(2), forced expiratory volume in the first second [FEV(1)] 48±15%predicted, six-minute walking test [6MWT] 464±84m and 84±16%predicted), whereas 10 patients were excluded from the test-retest reliability analysis due to missing data, resulting in a sample of 20 subjects for this purpose (50% male, 62±8years, BMI 27±6Kg/m(2), FEV(1) 48±15%predicted, 6MWT 452±93m and 82±19%predicted). Both samples were similar regarding general characteristics (P>0,05 for all variables). MDP presented strong correlations, i.e., ICC intra-rater: A1: 0.77 (0.48–0.90), S: 0.78 (0.52–0.91), and A2: 0.85 (0.66–0.94), with high internal consistency (Cronbach's α 0.86, 0.88 and 0.92 respectively); and ICC inter-rater: A1: 0.74 (0.46–0.89), S: 0.75 (0.48–0.89) and A2: 0.91 (0.78–0.96) with Cronbach's α 0.85, 0.86 and 0.95 respectively. CONCLUSION: The Portuguese version of the MDP is the first valid and reliable instrument to assess dyspnea multidimensionally in Portuguese-speaking patients with COPD.